Long-Term Impact Evaluation of Ground-Base Skidding on Residual Damaged Trees in the Hyrcanian Forest, Iran - Sattar Ezzati; Akbar Najafi (International Journal of Forestry Research)
We investigated the long-term effects of ground-base skidding on residual damage severity on the healing of residual damaged trees in forests of northern Iran twenty-years post logging operation. Characteristics examined included wound size, location, severity, height from ground level, number of wound on the damaged tree stems, and distance of damaged tree from centerline of the skid trail on a 8-meter distance alongside the abandonment skid trail. There were some crucial changes in the characteristics of the wounds on the damaged trees stems, which have been investigated on the high traffic intensity and the low traffic intensity. Results showed that an average amount of damaged trees alongside skid trails, which were 100% inventoried, were 18.83%. Results also confirmed that based on the available measurements of a twenty year period, it is too early to make any definite conclusion about how long it will take for occlusion of wounds on tree stems to fully heal from timber operations.